2016
DOI: 10.1021/jacs.5b12061
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme Catalysis with a Twist: Active State of the Twister Ribozyme in Solution Predicted from Molecular Simulation

Abstract: We present results from molecular dynamics simulations and free energy calculations of the twister ribozyme at different stages along the reaction path in order to gain insight into its mechanism. Results, together with recent biochemical experiments, provide support for a mechanism involving general acid catalysis by a conserved adenine residue in the active site. Although adenine has been previously implicated as a general acid acting through the N1 position in other ribozymes such as the hairpin and VS ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
76
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 39 publications
(116 reference statements)
12
76
0
Order By: Relevance
“…Based on molecular modelling simulations, the authors observed that rotation of U-1 towards A34 brought the nucleobase to the expected position underneath G33 with the O2′ atom presenting the required in-line orientation for the nucleophilic attack. Based on restrained molecular dynamics (MD) simulations, Gaines and York explored different conformational states of U-1 in Oryza sativa twister ribozyme and confirmed the existence of the two previously described conformations, termed as extruded and stacked [22].…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Based on molecular modelling simulations, the authors observed that rotation of U-1 towards A34 brought the nucleobase to the expected position underneath G33 with the O2′ atom presenting the required in-line orientation for the nucleophilic attack. Based on restrained molecular dynamics (MD) simulations, Gaines and York explored different conformational states of U-1 in Oryza sativa twister ribozyme and confirmed the existence of the two previously described conformations, termed as extruded and stacked [22].…”
mentioning
confidence: 58%
“…Lilley and co-workers suggested that the origin of this shift must be found in the local environment, since the six-membered ring of A1 lies between three phosphate groups [23]. This pKa shift was predicted by Gaines and York from computational simulations that rendered a variation of the pKa at the N3 position of A1 towards neutrality by approximately five units [22].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…To complement our experiments, we explored the self-cleavage step by simulating the activated precursor (AP) state33 being the HpRz structure closest to the transition state (see below for more details), using large-scale replica-exchange molecular dynamics simulations at HHP conditions. Fortunately, we could build on a rich available literature on force field molecular dynamics simulations of RNA or ribozymes at ambient conditions as documented, for instance, in refs 34, 35, 36 among many other works. Importantly, recently improved force fields3738 have enabled fairly reliable such simulations up to long time scales39.…”
mentioning
confidence: 99%
“…All of these MD trajectories were analyzed to investigate the role of the Mg 2+ ions in twister ribozyme and to examine possible candidates for the general base and acid in the self-cleavage mechanism. During completion of this work, a computational study of the O. sativa twister ribozyme, which has a sequence different from that of the env22 twister ribozyme studied herein, was published; 31 a brief comparison of these two studies is presented in the Conclusions.…”
mentioning
confidence: 99%